THE EFFORT OF LIFE SKILL PROGRAMS IN GROWING THE DEVELOPMENT OF CITIZEN ENTREPRENEURS, LEARNING CIVILITY PAKET C PKBM AZ-ZAHRA - Juju Juariah (Empowerment : Jurnal Ilmiah Program Studi Pendidikan Luar Sekolah, 2020)
The background of this research is the low data for entrepreneurs in Indonesia reaching 3.1 percent of the population of around 260 million people or around 8.06 million people, so that the PKBM management seeks to improve through entrepreneurship programs as an alternative towards self-reliant learning citizens. The purpose of this research is to find out how the efforts of life skill programs in developing the entrepreneurial spirit of citizens learn the equality of the Paket C PKBM Az-Zahra. The theory used in this research is the theory of life skills, entrepreneurship, equality, and PKBM theory. Researchers used interview and observation techniques with qualitative descriptive methods with qualitative approaches to obtain information from informants. The sample in this study was a PKBM manager, one tutor, and five students of the Az-Zahra PKBM Paket C was randomly selected. The results of the research are the efforts of the program to grow and develop the spirit of entrepreneurship already running, but it still needs to be developed in accordance with existing theories. The conclusion is that the life skill program is already running, but to foster an entrepreneurial spirit an innovative learning process needs to be carried out and it provides motivation so that students can become entrepreneurs after graduation instead of being employees in factories